Biodiversity of Freshwater Mitosporic Fungi from Dhule District (M.S.), India - Nemade2, S. Y. Patil1*, V. R. Patil2; L. C. (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-family: ’Times New Roman’;">Five species belonging to two genera of Hyphomycetes were isolated from foam samples and submerged leaves collected from the river Panzara in Dhule district. Flabellospora acuminata Descals and Webster is being reported for the first time from India. While Flabellospora crassa Alasoadura and Flabellospora multiradiata Nawawi are being reported for the first from Maharashtra state. <span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-family: ’Times New Roman’;">— 1P. G. Department of Botany, S.S.V.P.S.L.Kr.Dr.P.R. Ghogrey, Science College, Dhule (M.S.), India 2Shri V. S. Naik Arts, Commerce & Science College, Raver District- Jalgaon. 425508 (M.S.), India — Please Cite This Article As: Â S. Y. Patil, V. R. Patil and L. C. Nemade. 2010. Biodiversity of Freshwater Mitosporic Fungi from Dhule District (M.S.), India. J. Ecobiotechnol. 2(6):25-28. Â Â